Kreativitas Siswa Dalam Penggunaan Gadget Pada Pembelajaran PAI Di Masa Covid-19 - Ira Mauladina; Febri Giantara (LPPM STAI Diniyah Pekanbaru, 2020)
The use of gadgets in addition to communication can also be used to support the learning process. The learning process during covid 19 takes place online. One of the media used for the continuity of the online learning process is gadgets. Learning during the Covid 19 pandemic requires student creativity in the learning process. Problems in the field have been used by students to access social media and play online games. The formulation of the problem in the study wanted to see how the creativity of students using gadgets in the online learning process during the Covid 19 period. This study took a sample of SMA / MA equivalent students with the consideration that these students used the most gadgets. The results of observations and interviews found a pattern that gadgets besides helping to make the online learning process run also had a negative impact on being used by students to access social media and play online games. Whereas for student creativity that is associated with the theory of creativity, there is an activity of creating something that previously did not exist and was not done by someone, so it can be said that student creativity is still not running completely.